Posebnosti laboratorijske medicine v pediatriji - Levstek, Tina (Laboratorijska medicina, 2021)
Pediatric laboratory medicine covers a very wide peri-od from birth to adolescence. Due to rapid and intense growth and development during this period, pediatric la-boratory medicine faces many challenges. The differen-ces in laboratory test results do not only reflect the chan-ges associated with pathophysiological processes but also mirror growth and development. In this review article, we list the most common problems encountered by laboratory workers and clinicians in pediatric laboratory diagnostics from preanalytical and analytical factors to reference valu-es and tests that are usually unique to pediatric diagnostics. It is important to be aware of a special approach in pedia-tric medicine, as significant differences exist in sample co-llection, test performance, test interpretation, and disease frequencies. Despite many challenges, pediatric laborato-ry medicine makes an important contribution to diagno-sis and, consequently better treatment of infants, children, and adolescents. Close collaboration between specialists in laboratory medicine and clinicians is paramount to im-prove health outcomes in this age group.
Keywords: child; laboratorijska diagnostika; laboratorijska medicina; laboratory medicine; otroci; pediatrics; pediatrija